An analysis of accounting graduates skills and accounting professions : a case of UiTMT’s degree accounting graduates / Mustaffa Mohamed Zain ... [et al.] - Mohamed Zain, Mustaffa; Mohamed, Norazamina; Mustafa, Fadhilah; Hashim, Jamalludin Helmi (2005)
Given numerous calls from the accounting profession to emphasize non- technical skills in accounting program, it seems appropriate and important to ascertain whether that message has reached students. This study examines the perception of 166 accounting graduates and 50 employers toward non-technical skills mainly intellectual skills, interpersonal skills and communication skills. Accounting graduates perceived that all the three skills are equally important in securing the jobs. However, communication skills received the highest mean as compared to intellectual skills and interpersonal skills. The perception of employees who worked in accounting related field towards these skills is similar to those who worked in other professions. Communication skills again received the highest mean. It seems that all the professions are in consensus that communication skills are the most important skills as compared to intellectual skills and interpersonal skills. This finding supports the studies done by Estes’s (1979), Banhan (1995) and Nellermoe et al. (1999). Employers also value these 3 skills as equally important to their organization. These skills have been highlighted as correspondingly significant in AECC 1990 and Kullberg et al 1989 (cited in Elias 1999). Both employers and employees who are in accounting professions and non-accounting professions share the same view that the 3 skills are equally important to them. On the other hand, this study reveals that even though intellectual skills, interpersonal skills and communication skills are perceived important to employees and employers these skills do not have significant influence over students’ employability in accounting or non-accounting profession. The study also reveals that the importance of intellectual skills, interpersonal skills and communication skills begins to diminish when experience comes into picture. Students ranked lack of experience as their first hurdle towards securing their jobs. They view experience as the key indicator to secure jobs. This finding hopefully will be extended further in other studies that is to explore the needs of having proper first hand working experience (practical training) to be included at all level of accounting programs (diploma and bachelor). Some studies have revealed that internship is one of the valuable experience for students to be employable (Klein & Levy 1993, Pasewark et al. 1988, Pavlock 1977, Wright 1977 cited Oliver, Thomas W. & Que, Antonio L.1996). Therefore, suffice to say that accounting graduates could benefit from greater awareness of the importance of non-technical skills together with some experience before their jobhunting session begins.